A study of the inheritance of follicle and fleece characteristics in merinos, New Zealand romneys and their crossbred progeny : a thesis in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University - Meikle, Heather Elizabeth (Massey University, 1987)
A study was carried out to investigate the inheritance of follicle and fleece characteristics in Merinos, New Zealand Romneys and their crossbred progeny under North Island conditions. A total of 637 animals were sampled from the Ministry of Agriculture and Fisherie's flocks at Tokanui. It should be noted that the Romneys studied, were not the parents of the crossbred animals. Six flocks were sampled. Least squares means of the Romneys, Superfine Merinos, Local Merinos, Superfine Merino x Romneys, Local Merino x Romneys and Backcross (3/4 Superfine Merinos) were respectively as follows: secondary to primary follicle ratio (S/P), 6.68, 18.06, 18.66, 10.92, 10.32 and 15.81; follicle density n(P+S), 35.73, 69.69, 82.07, 49.57, 45.92 and 73.60; primary follicle density (nP), 4.72, 3.70, 4.23, 4.12, 4.23 and 4.40 and mean fibre diameter (MFD) 37.26, 20.71, 22.56, 26.24, 28.23 and 21.21. Of the fixed effects tested (age, birth/rearing rank and year of sampling) only age exerted a significant effect on most fleece and follicle characteristics. The repeatabilities for all follicle characteristics were greater than 0.4. Most objectively measured fleece characteristics also showed moderate levels of repeatability. Heritability estimates for follicle characteristics, calculated from small numbers ol daughter/dam pairs, were moderate to high. Phenotypic and genetic correlations for 21 fleece and 7 follicle parameters are reported on data corrected and uncorrected for fixed effects. An attempt was made to predict S/P using stepwise multiple regression techniques, but the resultant equations had low accuracy. There was negative heterosis in both crossbred genotypes for most follicle characteristics. LWT showed the highest level of positive heterosis. Methods of main gene detection were used to investigate the underlying genetic factors controlling follicle inheritance. Although follicle data had skewed distributions there was little evidence for genetic segregation for n(P+S). Multifactorial inheritance of n(P+S) was indicated. Two or more loci are possibly involved in the inheritance of S/P. The S/P genes appeared to behave in a recessive fashion. In contrast, the current results suggest the presence of a main gene for primary follicle density in both types of Merino x Romney flocks.
Keywords: Wool characteristics; Merino sheep; Romney sheep; Sheep breeding